Formulasi Kompos Limbah Black Soldier Fly (BSF) dan Tanah Sebagai Media Tanam Bayam (Amaranthus hybridus L) : Compost Formulation of Black Soldier Fly (BSF) Waste and Soil for Growing Spinach (Amaranthus hybridus L) - Haryanta, Dwi; Sa'adah, Tatuk Tojibatus; Pratiwi, Geby Sebrina Dian (Journal of Applied Plant Technology, 2022)
Black Soldier Fly (BSF) is a popular insect because of its role in breaking down organic waste into compost. The final stage of the larva (prepupa) separates from the growth medium making it easier to harvest. The residue of the propagation media is a mixture of the remaining organic matter with the larval skin resulting from the skin turnover into quality compost. This experiment aims to determine the effect of BSF residue compost on the growth and yield of spinach (Amaranthus Hybridus L); The experiment was carried out at the Green House and Laboratory of the Faculty of Agriculture, Wijaya Kusuma University, Surabaya, from March to July 2022. The factorial experiment, with the treatment of factor one was the composition of BSF waste compost which consisted of; P0 (soil : 100% compost : 0% soil without compost); P1 (soil: compost BSF household waste 75%: 25%); P2 (soil : compost BSF household waste 50% : 50%); P3 (soil: compost BSF fruit waste 75%: 25%); P4 (soil: BSF compost 50% fruit waste: 50%); while the second treatment factor is the application of urea fertilizer, namely: K0 without urea fertilizer; K1 was given 1.5 grams urea/plant ; K2 was given urea 3.0 g/plant. The results showed that there was an interaction between compost treatment and urea fertilizer treatment on spinach production. There was a significant difference between plants that were not given compost and plants that were treated with compost for the variables of consumption weight, total plant weight and root weight. Urea fertilizer treatment has a significant effect on spinach yield.